Modelo de seleção de times de desenvolvimento de projetos de software com abordagem adaptativa: um caso de uma empresa do ramo financeiro - Bergamini, Bruno Iwamoto (2024)
Projects with an adaptive approach require attention to the acquisition process due to their dynamic scope characteristics, challenging the contracting model. Therefore, this study aims to propose a general model for selecting software development teams using an adaptive approach within a financial company. The model developed in this study is relevant for project professionals as it aims to appropriately select development teams, thus preventing wastage of time and resources, and promoting the project, its stakeholders, and even the organization's reputation. To achieve this, a qualitative approach was used through the Design Science Research (DSR) method. To build the DSR steps, a Systematic Literature Review and a pilot case study were conducted to collect relevant data for model construction. Furthermore, a single case study was used to apply the proposed model and analyze the results. Data collection was conducted through interviews and non-participant observation of the project. As a result, the following outcomes were achieved: [1] assertiveness in supplier selection; [2] a procurement model more aligned with the project's needs; [3] increased collaboration among the parties; [4] as well as mutual trust; [5] an assertive assessment throughout the project life cycle; and [6] the generation of a knowledge base for future procurements. This study contributes to the literature on procurement in agile projects, providing valuable insights for professionals seeking efficiency in project management, with the potential to influence real-world practices.